Case report: The utilization of crizotinib and brentuximab vedotin as a bridge to autologous stem cell transplantation and followed by CD30-directed CAR-T cell therapy in relapsed/refractory ALK+ ALCL - Liu, Wanying; Wu, Jiaying; Ming, Xi; Zhang, Qi; Zhou, Delian; Zheng, Rubing; Zhou, Mi; Shang, Zhen; Chen, Liting; Zhu, Xiaojian; Xiao, Yi (Frontiers in Immunology, 2024)
Background Anaplastic lymphoma kinase-positive anaplastic large cell lymphoma (ALK+ ALCL) is a rare, mature T-cell non-Hodgkin lymphoma. The prognosis of patients with relapsed or refractory ALCL following first-line chemotherapy is extremely poor. NCCN guidelines recommend intensified chemotherapy with or without ASCT consolidation for r/r ALCL, however, this is not an effective treatment for all ALK+ALCL. Case report Herein, we report a patient with relapsed/refractory ALK+ ALCL who received crizotinib and brentuximab vedotin as bridging therapy, followed by autologous stem cell transplantation and sequential anti-CD30 CAR T cell therapy. Conclusion The patient achieved complete remission and long-term disease-free survival of months and continues to be followed up. The combination therapy model in this case may provide guidance for the management of relapsed/refractory ALK+ ALCL, and further prospective trials are needed to confirm its effectiveness.